Agroforestry enhances biological activity, diversity and soil‐based ecosystem functions in mountain agroecosystems of Latin America: A meta‐analysis - Anna M. Visscher; Paula Meli; Steven J. Fonte; Gianmaria Bonari; Stefan Zerbe; Camilla Wellstein (Global Change Biology, 2024)
Mountain agroecosystems in Latin America provide multiple ecosystem functions (EFs) and products from global to local scales, particularly for the rural communities who depend on them. Agroforestry has been proposed as a climate‐smart farming strategy throughout much of the region to help conserve biodiversity and enhance multiple EFs, especially in mountainous regions. However, large‐scale synthesis on the potential of agroforestry across Latin America is lacking. To understand the potential impacts of agroforestry at the continental level, we conducted a meta‐analysis examining the effects of agroforestry on biological activity and diversity (BIAD) and multiple EFs across mountain agroecosystems of Latin America. A total of 78 studies were selected based on a formalized literature search in the Web of Science. We analysed differences between (i) silvoarable systems versus cropland, (ii) silvopastoral systems versus pastureland, and (iii) agroforestry versus forest systems, based on response ratios. Response ratios were further used to understand how climate type, precipitation and soil properties (texture) influence key EFs (carbon sequestration, nutrient provision, erosion control, yield production) and BIAD in agroforestry systems. Results revealed that BIAD and EFs related to carbon sequestration and nutrient provisioning were generally higher in agroforestry systems (silvopastoral and silvoarable) compared to croplands and pasturelands without trees. However, the impacts of agroforestry systems on crop yields varied depending on the system considered (i.e., coffee vs. cereals), while forest systems generally provided greater levels of BIAD and EFs than agroforestry systems. Further analysis demonstrated that the impacts of agroforestry systems on BIAD and EFs depend greatly on climate type, soil, and precipitation. For example, silvoarable systems appear to generate the greatest benefits in arid or tropical climates, on sandier soils, and under lower precipitation regimes. Overall, our findings highlight the widespread potential of agroforestry systems to BIAD and multiple EFs across montane regions of Latin America.